The Effectiveness of TGT Learning Model on Writing Ability in Pandemic Timeline: A Qualitative Meta-Analysis - Ulfa, Anis Mahzum Alfita; Abid, Nuskhan (Universitas Pahlawan Tuanku Tambusai, 2025)
TGT Learning Technique (Team Game Tournament) is one of the populer teaching strategies. The learning process is no longer just listening to knowledge from teachers to students, but prioritizes the active role of student in the learning process. The purpose of this study is to determine the effectiveness of TGT in improving writing skills during the Pandemic timeline. The methodology used is qualitative meta-analysis by analyzing articles with PRISMA diagram, that published in the period from 2015-2024. The results showed that the use of TGT method was effective to increase students' learning motivation, increase students' interest and participation despite the distance and lack of direct interaction, and make it easier for students to understand and write better